Darmstadt as Refectory (Mess Hall) - Rea, John (Circuit, 2005)
John Rea followed up his term as composer-in-residence in Mannheim with an immersion in the 1984 summer courses. Here the Canadian composer relates a series of anecdotes, which include his surprise at being recognized (or actually not recognized) as the composer of Pincer la musique aujourd’hui, and his subsequent attendance at a concert of Xenakis's music accompanied by Morton Feldman, who later shared a number of secrets with him. This leads the author to a reflection on the Darmstadt of his generation, and that of today.